Effect of Combination of Different Antibiotics and Promoters for Expressing Recombinant Darbepoetin in Stable CHO K-1 Cell Line: Evaluating Antibiotic Combinations to Improve Yield and Quality of Darbepoetin - Widekdo, Dwi purno; Widodo, Nashi; Rifa'i, Muhaimin; Jatmiko, Yoga Dwi (Journal of Tropical Life Science, 2025)
Antibiotics are key for successful molecular cloning techniques. Different antibiotics have different mechanisms of action, which leads to cell heath and a viable number of passages. Moreover, the suitability of the promoter also plays an important role in achieving a higher level of protein titter in the stable cell platform. Therefore, with plenty of options of antibiotics and promoters available, we need to determine the best combination of antibiotics and promoters, particularly for specific proteins of interest. Darbepoetin is a recombinant therapeutics protein with extra glycosylation to increase the half-life in the blood; this drug is used for the administration of CKD and leukemia patients. Blasticidin-S and puromycin were used as antibiotics, and CMV and EF-1 promoters were used in this experiment to evaluate the expression of recombinant darbepoetin for the protein model. CHO K-1 cell line was transfected with a plasmid carrying a combination of promoter and antibiotics genes; after 14 days, the level of specific protein expression was evaluated using the western blot technique. A single clone cell was obtained using the serial dilution method to evaluate the clonality and expression of the protein of interest. This study successfully obtained a single clone from stable pool transfection. This result suggested that a combination of puromycin antibiotics and EF-1 promoter has promising expression compared to Blasticidin-S antibiotics with CMV promoter. For further conclusion, an analytical comparison of both combinations needed to be done.